Historical Aspects of the Development of Flax Growing in the Tobolsk Province in the Second Half of the XIX Century - V. V. Aksarin (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
The article is devoted to the history of flax growing and consideration of the experience of its development as an agricultural sector in the Tobolsk province. The material was the reviews, reports, descriptions and recommendations identified by the authors and devoted to this area of agriculture in the second half of the 19th century, among them: “Reviews of the Tobolsk province”, “Report on flax growing, flax production and flax trade in the northern region” by P. P. Chubinsky, “Instructions on how to benefit from agriculture or a description of the Turin district of the Tobolsk province economically” by priest M. Popov, “Harvest of grain in the Tobolsk province in 1894 and brief information about the state of agriculture” by N. L. Skalozubov. It is noted that the considered chronological period is poorly covered in the available literature, which contains only statistical information on the number of collected breads received from volost boards and from the appendices to the governor's reports. It is reported that the analysis of the situation in agriculture was carried out by local agronomists. It is emphasized that it was only in the early 1890s that the Tobolsk Provincial Committee attempted to systematize information on the state of agriculture in the province on the basis of data received from respondents living in rural areas and villages. The presented material reflects the main “milestones” of the development of flax growing in the Tobolsk province in agrotechnical, economic and economic aspects.